1996
DOI: 10.1002/j.2050-0416.1996.tb00892.x
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorometric Assay for Proteinase a in Beer and Its Application for the Investigation of Enzymatic Effects on Foam Stability

Abstract: A previously developed fluorometric assay using synthetic substrate, Succinyl-Arg-Pro-Phe-His-LeuLeu-Val-Tyr-4-methylcoumaryl-7-amide, for yeast proteinase A (PrA) was modified for the accurate and quick determination for the activity in unpasteurized beer. Employing simple HPLC for the deter mination of 7-amino-4-methylcoumarine (AMC), a final degradation product on this assay, the activity of PrA in beer was measured without the interference of the fluorogenic and photosensitive substance present in beer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…As a consequence, many researchers have focused on foam-positive species, in particular, beer proteins, which have been implicated to present in the production and stabilization of foam. The decrease in foam stability caused by yeast proteinase A (PrA) in unpasteurized beer has been reported by several researchers (Muldbjerg et al, 1993;Yokoi et al, 1996;Cooper et al, 2000;Wang et al, 2005;He et al, 2006). PrA is coded by PEP4 gene; construction of PEP4 yeast strains would be helpful to keep foam stability (Wang et al, 2007a).…”
Section: Introductionmentioning
confidence: 98%
“…As a consequence, many researchers have focused on foam-positive species, in particular, beer proteins, which have been implicated to present in the production and stabilization of foam. The decrease in foam stability caused by yeast proteinase A (PrA) in unpasteurized beer has been reported by several researchers (Muldbjerg et al, 1993;Yokoi et al, 1996;Cooper et al, 2000;Wang et al, 2005;He et al, 2006). PrA is coded by PEP4 gene; construction of PEP4 yeast strains would be helpful to keep foam stability (Wang et al, 2007a).…”
Section: Introductionmentioning
confidence: 98%
“…, 1980; Magni et al. , 1982; Yokoi et al. , 1996), but it was more difficult to purify the enzyme from yeast than from fresh beer because there were a lot of proteins similar to proteinase A in molecular size, and the enzyme activity was easily lost during the operations of chromatography (data and photograph were not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Proteinase A can be excreted into beer under stress or by yeast autolysis (Maddox & Hough, 1970) and is detrimental to beer foam stability (Dreyer et al. , 1983; Yokoi et al. , 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many experiments have shown that this phenomenon is due mainly to Proteinase A degradation of beer proteins 12 . To maintain the stability of beer foam, a number of studies have been conducted on Proteinase A to identify the relationship between Proteinase A content and foam stability 1,4,20,24,26 .…”
Section: Introductionmentioning
confidence: 99%